Canva Talking Presentation In Enhancing Speaking Proficiency: Students’ Perceptions - Wiyanah, Sri; Endahati, Nafisah (Universitas Muhammadiyah Tangerang, 2025)
This study aimed to explore students’ perceptions regarding the implementation of Canva talking presentation as a digital language learning tool. It adopted a case study design to respond the research problem with mixed-method approach. A questionnaire consisted of 27 statements was used to collect quantitative information focuses on students' opinions of Canva talking presentations in learning. Additionally, qualitative methods as interviews were used to understand students' experiences with Canva talking presentations, exploring the causes, challenges, and overall learning process. The study employed 28 students as participants. The study found that 82.2% of students were motivated to improve their English, and 85.7% felt more confident. Most students mentioned the project helped improve their vocabulary (82.1%) and overall English skills (96.4%). Canva Talking Presentation helps improve students' speaking skills but needs some adjustments. Students faced issues with technical problems, pronunciation, grammar, and repeating to be accurate, showing areas to improve.Keywords: canva talking presentation, speaking skills, students’ perception